Impact of healthcare-associated infections on the hospitalization costs of children - Leoncio, Jackeline Martins; Almeida, Vanessa Fraga de; Ferrari, Rosângela Aparecida Pimenta; Capobiango, Jaqueline Dario; Kerbauy, Gilselena; Tacla, Mauren Teresa Grubisich Mendes (Revista da Escola de Enfermagem da USP, 2019)
Objective To evaluate the impact of Healthcare-Associated Infections on the hospitalization cost of children. Method A prospective, quantitative cohort study involving children admitted to the Inpatient and Pediatric Intensive Care Units of a public university hospital. The data were analyzed through SPSS software by frequency distribution, central tendency measures and dispersion. The level of statistical significance was set at p<0.05 for all analyzes. Results The sample consisted of 173 children, of whom 18.5% developed Healthcare-Associated Infections, which increased the hospitalization costs 4.2 times (p<0.001). A greater cost impact was observed among patients with two or more infectious sites (R$81,037.57; p=0.010) and sepsis (R$46,315.63; p<0.001). Children colonized by multiresistant microorganisms with a prevalence of E. coli and A. baumannii ESBL also generated higher costs of R$35,206.15 and R$30,692.52, respectively. Conclusion Healthcare-Associated Infections significantly increased the hospitalization costs for children, especially among those with more than two infectious sites, who developed sepsis or were colonized by multiresistant microorganisms.